In Situ Conservation of Wild Orchid Species Diversity in Papua at the Base Camp of PT. Wijaya Sentosa, Teluk Wondama Regency, West Papua - Peday, Hans F.Z.; Anggrianto, Rusdi; Mosmafa, Frans E.; Matani, Onasius P.; Tasik, Susanti; Arobaya, Agustina Y.S. (Jurnal Biologi Papua, 2025)
This study aims to preserve the diversity of orchid species that are used as useful plants and have economic value. The methods used in this study are exploration, observation, species description. The technique used in sampling was carried out purposively when orchid species were found in the roaming area which was carried out randomly in an area of 10 hectares. It was revealed from the results of observations that 128 individuals were collected which were classified into 25 genera and 31 species were identified. The observed orchid habitus lives as epiphytic and terrestrial or lithophytic plants. Generally, species that live as epiphytes are more often found. Orchid habitats can be significantly distinguished in lowland tropical rainforests and swamp forests with humidity ranging from 80-85% and temperatures between 26-28% at night and 30-34% during the day. Topographic conditions are relatively flat to a slope of 45%. Vegetation cover is quite dense, but in some location, there are gaps in the canopy, providing opportunities for breakthroughs in sunlight intensity during the day. Conservation efforts are carried out on species that are often hunted and used as ornamental plants such as Bulbophyllum phalaenopsis, Coelogyne beccarii, Coelogyne asperata, Dendrobium antennatum, Dendrobium macrophyllum, Dendrovium shiraishii, Dendrobium spectabile, Grammatophyllum scriptum, Grammatophyllum speciosum and Pomatocalpa marsupiale. The Conservation Status of the collected species is generally categorized under IUCN Redlist as Data Deficiency (DD) and Least Concern (LC) clusters .